Road Pricing for Heavy Goods Vehicles Transport. Assessing the Economic Impact in a Disaggregated Macroeconometric Model - Kurt Kratena; Wilfried Puwein (Austrian Institute of Economic Research (WIFO), 2002)
The paper assesses the economic impact of a toll imposed on heavy-goods vehicles proportional to distance driven. The macroeconomic impact of the toll is estimated by using the disaggregated econometric model MULTIMAC of the Austrian economy. The assumption is that all toll revenues will be invested in the network of motorways. The toll is implemented in the model by using information on transport margins from the Austrian input - output statistics. The toll is distributed among goods in different categories of use (exports, consumption, intermediate demand) and thereby increases prices of demand (but not of production). The transport input row in the input - output matrix is changed according to the price elasticities taken from the literature. The toll will raise domestic prices especially for mineral products and the oil processing industry. Due to investment of the revenues the toll will increae GDP. The number of employed will rise in line with GDP and unemployment will drop slightly. The relative price increase of domestic production and the domestic final demand increase (investment) will reduce exports and boost imports leading to a deterioration of the foreign trade balance.
Keywords: E17; C67; L91; 330; Road Pricing; Macroeconometric Model; Maut; Güterverkehr; Wirkungsanalyse; Schätzung; Österreich